THE THEORITICAL FEASIBILITY OF INTERACTIVE HANDBOOK ON THE MUSCULAR TISSUE SENIOR HIGH SCHOOL CLASS XI - SILFIA PUTRI, TERA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
One of learning components which is developed to support improvement of student’s quality is a handbook. A handbook as a means of communication should be developed better so that there is an interaction between students and the book. This research aims were to produce an interactive handbook on the sub material of human muscular tissue and to describe the theoretical feasibility of interactive handbook based on expert’s evaluation. This research was conducted using Kemp model. The result showed that the developed interactive handbook was very worthy with validation value about 91.61%. Keywords: interactive handbook, Kemp model, human muscular tissue